1963
DOI: 10.6028/jres.067a.025
|View full text |Cite
|
Sign up to set email alerts
|

Purity analysis of highly purified materials by time-temperature cryometry

Abstract: Visual observation of the freezing and melting of compounds in cells used for the determination of purity has uncovered some heretofore unexpected behavior. This behavior has been correlated with certain difficulties experienced in the measurement of purity, particularly when the sample is very pure. Means for partially reducing these difficulties are proposed and procedures for increasing the accuracy of purity measurements are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1963
1963
1972
1972

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Two difTerrent samples of benzene were a nalyzed . In t i1e first saillple the purity as determined by t he m ethod described he rein was co mp ared wi th t he plll'ity as determined by t ime-temp erftt ul'C a nalysis usin g a 50-ml sa mple [2,3]. vVhen th e second sample was analyzed a portion of the sa mple was placed in the small, gold-van ed cell a nd a nother identical portion was distilled into an all-glass cell, similar in shape and size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two difTerrent samples of benzene were a nalyzed . In t i1e first saillple the purity as determined by t he m ethod described he rein was co mp ared wi th t he plll'ity as determined by t ime-temp erftt ul'C a nalysis usin g a 50-ml sa mple [2,3]. vVhen th e second sample was analyzed a portion of the sa mple was placed in the small, gold-van ed cell a nd a nother identical portion was distilled into an all-glass cell, similar in shape and size.…”
Section: Methodsmentioning
confidence: 99%
“…The results of t hese analyzes were, respectively, 99.985 a nd 99.980 mole percent. vVben 50 ml of the sample was analyzed thermometrically [3], the purity was calculated to be 99.976 mole percent.…”
Section: Methodsmentioning
confidence: 99%
“…The two other techniques effectively depend on heat content. They are adiabatic calorimetry [3, 4] and time-temperature (thermometric) freezing curves [5, 6]. A carefully conducted comparison [7] has shown that the three techniques, each at its best, can give reliable results.…”
Section: Cryometric Methodsmentioning
confidence: 99%
“…Pull details of the method were disclosed at the EURATOM Conference on High -Precision Analysis of Substances of Interest to Nuclear Chemistry, January [18][19][20][21][22]1965 [8] , and will be published in the near future.…”
Section: Facilitiesmentioning
confidence: 99%
“…The purity values of the presently available NBS standard reference materials of hydrocarbons were obtained by this method. Examples of more recent results and comparisons of this method against the other cryoscopic techniques have been published [18,19].…”
Section: The Cryometric Cell Is Described In Detail By Glasgow and Tementioning
confidence: 99%